IMPLEMENTASI MANAJEMEN KURIKULUM 2013 DI MTsN PANDEGLANG PROVINSI BANTEN - Utami, Try Septy Tanys (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2018)
This paper discusses a curriculum design and comprehensive learning plan, in a school it is necessary for management to organize an organization and manage activities to be carried out, besides curriculum management is also designed so that planning, implementation and evaluation of the curriculum runs more effectively, efficiently and optimally in empower learning resources, experience and curriculum components. This study uses a qualitative approach with data collection techniques through observation, interviews, and document studies through a descriptive approach, in the form of words, writing or oral and description. Data analysis techniques are done through data collection, reduction, data presentation, drawing conclusions and steps to test the validity of the data using triagulation techniques.The results of this study reveal that: 1) Implementation of 2013 curriculum management at MTsN 1 Pandeglang so that teachers have more understanding of the curriculum. 2) Implementation of curriculum management programs or programs at MTsN 1 Pandeglang in the implementation of the activity committee and the division of tasks of the teachers who carry out their tasks and functions, so that school activities or programs can be organized. 3) Inhibiting factors and supporting factors for implementing curriculum management as a whole there are no school barriers from internal schools that complicate the implementation of planning, implementation, and evaluation of curriculum management, 4) Strategies or steps in overcoming these obstacles are by implementing the working meeting, there is also an evaluation on The Student Conference held in the middle of the year involving homerooms, field staff, and the headmaster. Keywords. Implementation, Curriculum Management, Planning, Implementation, Evaluation